2020
DOI: 10.35631/ijemp.39002
|View full text |Cite
|
Sign up to set email alerts
|

Green Supply Chain Management Practices: A Literature Review

Abstract: Evidence that green supply chain management is one of the best practices contributing to economic and environmental performance has been acknowledged in the literature. The purpose of this study is to review 100 articles on green supply chain management practices from the year 2000 until the year 2019. A content analysis methodology was employed to classify the articles. Approximately 100 articles on green supply chain management practices were analysed using SPSS 22 to determine the frequency and percentage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Content analysis methodology has been successfully used in several studies to classify and analyze reviewed literature in multiple disciplines, such as supply chain management (SCM) and logistics (e.g. Sachan and Datta, 2005;Ibrahim et al, 2015;Wu et al, 2017;Razak and Ibrahim, 2020;Nagariya et al, 2021), TQM (e.g. Evans et al, 2014) (Vespestad and Clancy, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Content analysis methodology has been successfully used in several studies to classify and analyze reviewed literature in multiple disciplines, such as supply chain management (SCM) and logistics (e.g. Sachan and Datta, 2005;Ibrahim et al, 2015;Wu et al, 2017;Razak and Ibrahim, 2020;Nagariya et al, 2021), TQM (e.g. Evans et al, 2014) (Vespestad and Clancy, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…From these perspectives, it has been found that such practices can lead to reductions in greenhouse gas emissions and other environmental impacts. However, GSCM is a complex phenomenon and has yet to be thoroughly explored in the context of ERs and CSR [36,37]. Therefore, this research explores the GSCM with CSR and ERs in agri-food business.…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
“…Being purchasing the starting point in a supply chain, and having implications downstream along the supply chain, the implementation of the environmental and social practices, should start at this phase (Rao & Kondo, 2010). In academia and business, the interest in the cross-disciplinary area of green purchasing/procurement (GP) research continues to grow mainly motivated by environmental and financial performance in response to competition, regulation, and community demands (Che-Razak & Ibrahim, 2020). For most of the companies environmental awareness has become a must rather than a choice (Ghosh, 2019), causing the revision of their production processes and supply chains with respect to environmental aspects since they are seen as the source of environmental problems (Yildiz-Çankaya & Sezen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on GSCM practices were conducted in Asia, specifically in China. In Europe only 16 articles were conducted and only 10 out of 100 articles were exploratory (case studies) in nature (Che-Razak & Ibrahim, 2020). Also, China, USA and India dominate this discipline in terms of their impact and number of publications (Tseng, Islam, Kariab, Fauzib & Afrin, 2019;Jabbour & Stefanelli, 2021), which justifies the need to do more studies in Europe using exploratory research.…”
Section: Introductionmentioning
confidence: 99%